Molecular based detection for drug resistance in mycobacterium tuberculosis (Medical Journal of Indonesia, 2003)
Multi- drug resistant tuberculosis continues to be a serious problem, particularly among some developing countries. Early detection of drug resistance in clinical M. tuberculosis isolates is crucial for appropriate treatment and to prevent the development of further resistance. Compared to conventional methods using solid media, the introduction of manual and automated methods (BACTEC or MB/BacT) for susceptibility testing in liquid media has resulted from 4 to 6 weeks to 3 to 15 days. The identification of resistance mutations, e.g., the genetic basis for RIF resistance, enables the development of molecular test that allows the detection of resistant strains within 1 day. One approach is the use of molecular analysis to detect mutations that are associated with resistance to drugs including INH and RIF. In the case of INH, mutations of the katG, inhA, kasA, and ahpC genes are responsible for the majority of INH-resistant M. tuberculosis, whereas mutations of rpoB are responsible for RIF-resistant M. tuberculosis. (Med J Indones 2003; 12: 259-65)